STUDY OF IMPORTANT VARIABLES OF AERODYNAMICS FOR SUBSONIC AIRCRAFT USING ADVANCED AIRCRAFT ANALYSIS SOFTWARE (Journal of Engineering, 2010)
This study presents the important variables of aerodynamics of subsonic aircraft using AAA software, moreover to comprehensive preview of some imperical and mathematical equations where needs in this analysis process. Cruise mission chose for this study comparing with another mission of flight such as Take-off, Climb, Dive & Descent, and Landing according to important of the mission and cruise mission has large rung during the flight mission. These analyses of process submit to more and complex iteration process until we access to correct solution. Lift, drag, and moment coefficients along the lift surfaces such as wing, and horizontal tail were showed. Also this paper explain the effect of flight level, aircraft speed, aspect ratio of lift surfaces on lift curve. Results show that, increase the value of altitude, load factor,aspect ratio leads to increase the value of lift coofficent and decrease the airplane velocity.